Membangun dan Mereka Bentuk Meja Putar bagi Menghasilkan Potongan Kayu Bulat dengan Gergaji Pita - Wagiman, Abdullah; Muhammad Ruzaini Md Rodzi; Muhammad Saiful Safwan Mat Farzi; Muhammad Nur Izwan Zulkifli; Hafsa Mohammad Noor; Suhairi Ismail (Multidisciplinary Applied Research and Innovation, 2024)
In the production of kompang, cutting the wood into rounds is an important step in the manufacture of the kompang’s frame. However, the cutting process is usually done manually or using a regular band saw machine which cannot produce a round shape accurately and efficiently. Therefore, the rotary table accessory has been designed as an addition to the band saw machine to increase the efficiency and safety of the rattle manufacturer. In today’s industry, there is still no machine capable of cutting wooden blocks into rounds. After going through the fabrication and testing process, turntable accessories may need some repairs or design adjustments to improve their performance. If there is a weakness or defect in the turntable accessory, remedial measures will be taken to ensure it works properly. Design improvements can involve modifying components, optimizing size and shape parameters, or improving the functionality and performance of turntable accessories. This process involves applying technical knowledge and competence in product design to produce the best version for the turntable.